2015
DOI: 10.1190/geo2014-0506.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the borehole quasistatic electric field excited by the acoustic wave during logging while drilling due to electrokinetic effect

Abstract: Acoustic logging while drilling (LWD) is an important commercial technology for oil and gas exploration. However, the collar wave in the full waveform has been found to interfere with signals from the formation, making it difficult to obtain formation compressional and shear velocities from acoustic LWD signals. We investigated seismoelectric LWD to solve this problem. We focused on the feasibility of obtaining the formation acoustic compressional and shear velocities from electric signals that go with acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…By comparing Figure 2a,b, Figure 4a,b and Figure 6a,b, it can be found that the electric field in the electrokinetic logging while drilling in the oil-wetted porous formation with dual phase fluid is much less affected by the drill collar wave than the acoustic field, which is an advantage of electrokinetic logging. This is consistent with the research results of saturated porous medium [14,15]. At the same time, it can also be found that under the excitation of dipole source, the influence of drill collar wave can be almost ignored.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By comparing Figure 2a,b, Figure 4a,b and Figure 6a,b, it can be found that the electric field in the electrokinetic logging while drilling in the oil-wetted porous formation with dual phase fluid is much less affected by the drill collar wave than the acoustic field, which is an advantage of electrokinetic logging. This is consistent with the research results of saturated porous medium [14,15]. At the same time, it can also be found that under the excitation of dipole source, the influence of drill collar wave can be almost ignored.…”
Section: Discussionsupporting
confidence: 91%
“…Guan's research indicates that the electric field is less affected by the drill collar wave in the electrokinetic logging while drilling in saturated porous formation. In 2015, Zheng conducted a similar study using the quasi-static field method and obtained the same conclusion [15].…”
Section: Introductionmentioning
confidence: 73%
“…This slow convergence problem also affects the numerical simulation of elastic waves in stratified solid media (e.g., Apsel & Luco, 1983; Bouchon & Aki, 1977; Chen, 1999; Kennett, 1983; Yao & Harkrider, 1983). Classic methods for modeling the wave‐fields inside a borehole, for instance, real‐axis integration method (e.g., Tsang & Rader, 1979; Zheng et al., 2015), and discrete wavenumber method (e.g., Cheng & Toksöz, 1981), can also encounter the same problem (e.g., Parra et al., 1993). Two methods have been proposed to solve this problem.…”
Section: Problem Analysismentioning
confidence: 99%
“…They calculated ES and SE logging responses to estimate the parameters of the porous medium around the borehole. A variation of this numerical technique was employed recently by Zheng et al [2015] when simulating the electric field excited by the acoustic wave in a logging while drilling scenario. Two dimensional numerical tests about P-TM conversions using an implicit time stepping finite element algorithm in a commercial software were implemented by Kröger et al [2014], while Zhou et al [2014] studied converted waves inside a borehole setting boundary conditions at the interface between fluid and porous media.…”
Section: Introductionmentioning
confidence: 99%